2019
DOI: 10.1111/1468-5973.12282
|View full text |Cite
|
Sign up to set email alerts
|

Truth, trust, and civic duty: Cultural factors in citizens' perceptions of mobile phone apps and social media in disasters

Abstract: This study investigates how citizens perceive the role of mobile phone apps specifically designed for disaster communication, and how these perceptions may differ from perceived roles and functions of social media in disaster-related tasks/situations. Focusing on trust in authorities and technology use, results suggest that social media use not only fosters trust via shared narratives and collective sense-making but may also improve trust relationships through local authorities assuming the function of a trust… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(42 citation statements)
references
References 40 publications
1
40
0
1
Order By: Relevance
“…Assessing information needs is also essential for designing efficient citizen science tools. Indeed, citizens will use technologies that meet their needs, especially in case of disaster (Appleby et al, 2019). This confirms that citizen seismology projects should set up ways to obtain user feedback on a regular basis and co-build the tools.…”
Section: Understanding Information Needs and Cultural Backgroundmentioning
confidence: 70%
See 1 more Smart Citation
“…Assessing information needs is also essential for designing efficient citizen science tools. Indeed, citizens will use technologies that meet their needs, especially in case of disaster (Appleby et al, 2019). This confirms that citizen seismology projects should set up ways to obtain user feedback on a regular basis and co-build the tools.…”
Section: Understanding Information Needs and Cultural Backgroundmentioning
confidence: 70%
“…In order to communicate efficiently, information needs must be assessed locally as they vary depending on cultural factors as well as previous knowledge and experience. Research has found that the type of information, the legitimate and trusted actor, as well as the way the public want to receive it will vary depending on risk culture, technology culture, gender roles, age or religion for instance (Tagliacozzo and Magni, 2016;Appleby et al, 2019;Becker et al, 2019). This implies that scientific communication is an essential part of citizen science projects.…”
Section: Understanding Information Needs and Cultural Backgroundmentioning
confidence: 99%
“…Finally, trust is an essential, but a variable, aspect of the system -there is no guarantee that the data that is provided is accurate, but successful crowdsourcing systems find a way to validate data for veracity [44]. Furthermore, social media and disaster apps hold the potential to not only be useful tools in disaster communication between citizens and authorities based on existing trust, but they also have the ability to help in building, rebuilding, or strengthening trusted relationships [47].…”
Section: Self-organizing Operation Mechanisms Of Crowdsourcing In Thementioning
confidence: 99%
“…This review demonstrates that there are eight types of crisis under investigation namely managerial misconduct crisis such as the organizational and corporate crisis (e.g. [31]), natural crisis such as flood and storm cases (e.g. [32]), public health crisis such as the 2014 Ebola outbreak, Swine flu and Bird Flu cases (e.g.…”
Section: Types Of Crisis Under Investigationmentioning
confidence: 99%